Estimating the Value of Oil Capital in a Small Open Economy: the Venezuela's Example - Sara Aniyar (Fondazione Eni Enrico Mattei (FEEM), 2003)
The paper focuses in the calculation of the oil capital value in a small open economy depending on oil rents. The Venezuelan case is used as an example. In valuing the oil capital, two issues are recalled and discussed: how should the exploration costs and the capital gains be treated? It is shown that the estimations vary significantly depending on which set of assumptions are made about the way to account for them and the assumptions made about how the economy functions. It is argued that during the studied period the value of the Venezuelan stock of oil capital has increased, and it has done so faster than the population.
Keywords: D23; 330; Venezuela; Oil Capital; Capital Gains; Exploration Costs; Property Rights; Erdöl; Erdölvorkommen; Sachenrecht; Bewertung; Wertzuwachssteuer; Erdölgewinnung; Kosten; Allokation; Venezuela